2020
DOI: 10.3389/fchem.2019.00910
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Resonance as a Tool for Ligand Binding Investigation of Engineered GPR17 Receptor, a G Protein Coupled Receptor Involved in Myelination

Abstract: The aim of this study was to investigate the potential of surface plasmon resonance (SPR) spectroscopy for the measurement of real-time ligand-binding affinities and kinetic parameters for GPR17, a G protein-coupled receptor (GPCR) of major interest in medicinal chemistry as potential target in demyelinating diseases. The receptor was directly captured, in a single-step, from solubilized membrane extracts on the sensor chip through a covalently bound anti-6x-His-antibody and retained its ligand binding activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…http://www.mdckpred.in/ Regression model An intuitive way of prioritizing small molecules based on calculated MDCK permeabilities [ 404 ] Vienna LiverTox Prediction of interactions profiles of small molecules with transporters relevant for regulatory agencies. https://livertox.univie.ac.at/ Machine learning classification model Identify pharmacokinetic properties [ 405 ] Ambit-SMIRKS A software module for reaction representation, reaction search and structure transformation. http://ambit.sourceforge.net/smirks The Chemistry Development Kit Standardization of large chemical databases and pathway transformation database and prediction [ 406 ] COSMOfrag A Novel Tool for High-Throughput ADME Property Prediction and Similarity Screening Quantum Chemistry In the COSMO − RS picture, any molecular information is gathered in the so-called σ profiles, COSMOfrag replaces the single σ profile with a composition of partial σ profiles, selected by the use of extensive similarity searching algorithms [ 407 ] RosENet Predicting the absolute binding affinity of protein–ligand complexes Convolutional neural networks Combines voxelized molecular mechanics energies and molecular descriptors [ 408 ] MDeePred Novel multi-channel protein featurization for deep learning-based binding affinity prediction in drug discovery.…”
Section: Applications Of Artificial Intelligence In Drug Development mentioning
confidence: 99%
“…http://www.mdckpred.in/ Regression model An intuitive way of prioritizing small molecules based on calculated MDCK permeabilities [ 404 ] Vienna LiverTox Prediction of interactions profiles of small molecules with transporters relevant for regulatory agencies. https://livertox.univie.ac.at/ Machine learning classification model Identify pharmacokinetic properties [ 405 ] Ambit-SMIRKS A software module for reaction representation, reaction search and structure transformation. http://ambit.sourceforge.net/smirks The Chemistry Development Kit Standardization of large chemical databases and pathway transformation database and prediction [ 406 ] COSMOfrag A Novel Tool for High-Throughput ADME Property Prediction and Similarity Screening Quantum Chemistry In the COSMO − RS picture, any molecular information is gathered in the so-called σ profiles, COSMOfrag replaces the single σ profile with a composition of partial σ profiles, selected by the use of extensive similarity searching algorithms [ 407 ] RosENet Predicting the absolute binding affinity of protein–ligand complexes Convolutional neural networks Combines voxelized molecular mechanics energies and molecular descriptors [ 408 ] MDeePred Novel multi-channel protein featurization for deep learning-based binding affinity prediction in drug discovery.…”
Section: Applications Of Artificial Intelligence In Drug Development mentioning
confidence: 99%
“…In both cases, the use of GPR17 agonist resulted in a significant amelioration of OL differentiation and myelination capabilities. Indeed, the selective GPR17 agonist Asinex 1 promoted OPC maturation and myelination of dorsal root ganglion (DRG) neurons in vitro [ 202 ]. Of note, a recent in vivo study showed that the treatment with another selective agonist, named galinex, resulted in protection against EAE symptoms exacerbation [ 203 ].…”
Section: Emerging Therapeutics Targeting Ol Dysfunction Of Potentimentioning
confidence: 99%
“…ligands [29,31,44]. The docking solutions were ranked according to their predicted binding free energy values.…”
Section: Plos Onementioning
confidence: 99%
“…However, these results are not surprising since all compounds of Family I derive from a common scaffold with agonist activity. Of note, previous independent virtual screening on the receptor led to the identification of GPR17 agonists with demonstrated promyelinating activity on in vitro rodent models characterized by similar structure [23,31,44] and potency, suggesting that this scaffold may be suitable for defining a lead compound for GPR17. Moreover, this potency is in line with that of other class-A GPCR agonists [56], and of our previous set of novel GPR17 activators [31].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation